POPULATION DENSITY, SEASONAL ABUNDANCE AND NATURE OF DAMAGE OF THE LEAFHOPPER , EMPOASCA DECEDANS (PAOLI) (HOMOPTERA : CICADILLIDAE) ON CERTAIN CORN CULTIVARS . - M. AL-Hasnawi, M. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
Laboratory and field experliments were conducted at the college of Agriculture, university of Baghdad during the spring season , 2012 to estimate the population density, seasonal abundance and the nature of damage of the corn leafhopper on 4 cultivars of corn . The results was showed that the infestation with the leafhopper Empoasca decedans ( paoli) begining after seedling emergence. Symptoms characterized by the presence of yellow lines on leaves which turn into brown and kill of seedlings in severe infestation . Two peaks of the leafhopper were observed during the growing season ,the first high peak of 16/leafhapper /trap occure during the last week of April will the second peak of 9.6 leafhopper /trap occurred during the 3rd week of May. The American cultivar( pop- corn) was distingushed by its highest numbers of leafhopper of 16.66 leafhopper /sweep net , which significantly different from numbers of insect recorded to cultivar buhooth 106 ,IPA 5018 and kafer which amounted for 9.04 , 9.9 4 and 9.87 leafhopper /sweep net respectively. The highest percentage of leaf damage on the 1st , 2nd,3ed ,4th , 5th , and 6th leaves of 35% on pop corn , which significantly different from percentages of damage on other cultivars which amounting for 7.9, 14.5 and 21.4% for kafer , Buhooth 106 and IPA 5018 respectively . It seems that the leafhopper prefer to feed on old leaves in base of the seedling and then it moves gradually to upper leaves toward the top of plant . It is clear from these results that the American pop corn were the highest infestation to the Leafhopper E. decedans and the least was kafer .